The effects of total laser pubic hair removal on sexual functions, body perception and self-esteem in women - Aydos, Mustafa Murat; Önen, Sinay; Önen, Efe (The European Research Journal, 2020)
Objectives: Both males and females carried out pubic hair removal by various methods usually for visual/aesthetic or psychosexual reasons. The aim of the present study was to evaluate self-esteem, body image and sexual functions of women before and after total laser pubic hair removal (TLPHR) which is frequently being prefered due to its long-lasting effects. Methods: A total of 45 sexually active women between 20 and 50 years of age who underwent total laser pubic hair removal were included in the study. The sociodemographic features, Female Sexual Function Index (FSFI), Rosenberg Self Esteem Scale (RSES), Body Cathexis Scale (BCS), Beck Depression Inventory (BDI) of the participants were assessed before the first session and after the 6th session of TLPHR procedure. Results: Total RSES, total BCS scores and the 40th item of the BCS score significantly decreased after the TLPHR procedure (p < 0.001). Total FSFI scores and also FSFI subscales of desire, arousal, lubrication and satisfaction scores were significantly increased after TLPHR (p < 0.001). Conclusion: Our study results demonstrated that self-esteem, genital and total body image, sexual desire, sexual arousal and sexual satisfaction was improved after TLPHR procedure. Wider sampled studies examining the effects of laser pubic hair removal on individual, relational and psychosocial issues in both males and females are needed.